Features and Functions of Multifunctional Urban Agriculture in the Global North: A Review - Orsini, Francesco; Pennisi, Giuseppina; Michelon, Nicola; Minelli, Alberto; Bazzocchi, Giovanni; Sanyé-Mengual, Esther; Gianquinto, Giorgio (Frontiers in Sustainable Food Systems, 2020)
In recent years, urban agriculture (UA) projects have bloomed throughout the world, finding large applications also in the developed economies of the so-called Global North. As compared to projects in developing countries, where research has mainly targeted the contribution to food security, UA in the Global North has a stronger multifunctional connotation, and results in multiple combinations of farming purposes and business models pursued. The present review paper explores the contribution and role that UA plays in cities from the Global North, defining its functionalities toward ecosystem services (ES) provisioning and analysing the factors that hinders and promote its regional diffusion and uptake. The manuscript integrates a description of UA growing systems, as well opportunities for crop diversification in the urban environment, and a comprehensive classification of UA business models. The distinctive features in terms of business models, farming purposes and farm size are then applied over an inventory of 470 UA projects in the Global North, allowing for a characterization and comparative analysis of distribution frequency of the different project typologies.